Recent Publications (Quarterly Journal of Economics, 1958)
Recent Publications Get access The Quarterly Journal of Economics, Volume 72, Issue 3, August 1958, Page 475, https://doi.org/10.1093/qje/72.3.475 Published: 01 August 1958